Occlusion development after premature loss of deciduous anterior teeth: preliminary results of a 24-month prospective cohort study - Patricia NADELMAN; Eduardo Otero Amaral VARGAS; Guido Artemio MARAÑÓN-VÁSQUEZ; Ana Lúcia VOLLÚ; Matheus Melo PITHON; Amanda Cunha Regal de CASTRO; Lucianne Cople MAIA (Dental Press Journal of Orthodontics, 2024)
ABSTRACT Objective: This study aimed to evaluate occlusion development after premature loss or extraction of deciduous anterior teeth, by means of a prospective cohort study. Methods: Fifteen infants and children aged 1 to 5 years old were longitudinally assessed (with loss or extraction of deciduous anterior teeth [n = 9], and without tooth losses [n = 6]). Photographs and dental casts at the baseline and after 24 months of follow-up were performed. Dental casts were scanned, and linear measurements were made on the digitalized models (missing tooth space, arch perimeter, arch length, arch width, intercanine length and intercanine width). The t-test was used for groups comparisons (α = 0.05). Results: Individuals’ mean age at baseline was 2.93 (± 1.18) years. No statistically significant differences were observed in the missing tooth space in the group with tooth loss during the 24 months of follow-up (p > 0.05). Arch perimeter, arch length, arch width, intercanine length and intercanine width did not show differences between the groups (p > 0.05). Qualitative photographic evaluation revealed other changes in the dental arches and occlusion, such as exfoliation and eruption of deciduous teeth, eruption of permanent teeth, self-correction or establishment of malocclusion, among others. Conclusion: The results suggest that the premature loss of deciduous anterior teeth does not affect the perimeter, length and width of the dental arches; however, other alterations that lead to malocclusion could be established.